Nondegenerate two-photon absorption in ZnSe: Experiment and theory - Krauss-Kodytek, L.; Hannes, Wolf-Rüdiger; Meier, Torsten; Ruppert, C.; Betz, M. (Physical Review B)

Broadband coherent anti-Stokes Raman scattering for crystalline materials - Hempel, Franz; Reitzig, Sven; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Broadband coherent anti-Stokes Raman scattering (B-CARS) has emerged in recent years as a promising chemosensitive high-speed imaging technique. B-CARS allows for the detection of vibrational sample properties in analogy to spontaneous Raman spectroscopy, but also makes electronic sample environments accessible due to its resonant excitation mechanism. Nevertheless, this technique has only gained interest in the biomedical field so far, whereas CARS investigations on solid-state materials are rare and concentrate on layered, two-dimensional materials such as graphene and hexagonal boron nitride . In this work, we discuss the specific properties of this technique when applied to single-crystalline samples, with respect to signal generation, phase matching, and selection rules in the model systems lithium niobate and lithium tantalate. Via polarized B-CARS measurements and subsequent phase retrieval, we validate the predicted selection rules, unequivocally assign the phonons of the A1(TO), E(TO) and A1(LO) branches to the detected CARS peaks, and address differences in spontaneous Raman spectroscopy concerning peak frequencies and scattering efficiencies. We thus establish this technique for future investigations of solid-state materials, specifically in the field of ferroelectric single crystals.

Hybrid density functional theory benchmark study on lithium manganese oxides - Eckhoff, Marco; Blöchl, Peter E.; Behler, Jörg (Physical Review B)
Keywords: pc2-ressources

Electrostatic potential shape of gate-defined quantum point contacts - Geier, M.; Freudenfeld, J.; Silva, J. T.; Umansky, V.; Reuter, Dirk; Wieck, A. D.; Brouwer, P. W.; Ludwig, S. (Physical Review B)

Electrical detection of excitonic states by time-resolved conductance measurements - Ebler, C.; Labud, P. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Ludwig, A. (Physical Review B)

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Spin splitting in a MoS2 monolayer induced by exciton interaction - Li, Yao; Li, Guangyao; Zhai, Xiaokun; Xiong, Shifu; Liu, Hongjun; Wang, Xiao; Chen, Haitao; Gao, Ying; Zhang, Xiu; Liu, Tong; Ren, Yuan; Ma, Xuekai; et al. (Physical Review B)

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research